OBTAINING VIRUS FREE PLANTS FROM ASPARAGUS OFFICINALIS L. “Asparagus” IN VITRO - Quiñonez Aguilar, Mauro (2020)
This work attempts to obtain free virus Asparagus officinalis L. “garden asparagus”plants, applying the biotechnological methods of the in vitro meristem culture. Axillarybuds were used as explants, and were sterilized, isolated, cultivated in the basalmedium Murashige & Skoog (MS) at 3 different concentrations (0,5; 1,0 & 1,5 mg/L)of the phytohormone 6-Bencil Aminopurine (6-BAP), and incubated under controlledconditions in a cultivation room. As a result, 8 shoots & 8 cladodes, 6 shoots with nocladodes and 1 shoot & 5 cladodes were obtained in the culture mediums supplementedwith the 3 concentrations of 6-BAP respectively.